A study on economic traits, costs and returns of buffalo husbandry in Haryana - KUMAR, NIRMAL; SUHAG, K S; KUMAR, SHIV; KUMAR, DALIP; CHAUDHARY, KHYALI RAM (The Indian Journal of Animal Sciences, 2011)
The present study was taken up to study the economic traits of bovines i.e. buffalo, and to work out the cost and returns from buffalo milk production on different categories of herds in Hisar and Karnal. Buffalos are the main milch animals followed by the crossbred cattle to sustain the milk production needs in both districts. The age at first calving has considerable economic significance to the farmers because the cost of rearing heifer from birth to calving and consequently the milk yield are strongly influenced by this character. The average gestation period was almost same in both the selected district. On an average more than one service per conception was required. On an average duration of milk yield was 58 and 63 days in Hisar and Karnal district, respectively. The milk yield decreased with the increase in herd size in both the districts. As a result of economies of large size, labour cost decreased with increase in herd size in both the districts. The net maintenance cost per milch buffalo was highest in winter and lowest in rainy season on all the herd size groups. On an average the net profit of milk production of a buffalo per day was highest on small herd size group followed by medium and large size group in Hisar district. In Karnal district the net or gains per day was highest on small followed by large and medium herd size groups. The net profit per buffalo per day was higher in winter and lowest in summer in small herd size groups in Hisar district and on medium and large herd size groups in rainy season and lowest gain in summer. In Karnal district the trend was slightly different. The net return was highest in rainy season in all the herd size groups but lowest in summer in small, and in winter in medium and large herd size of groups. On an average about 48 and 58% of the total milk produced was sold as fresh milk in Hisar and Karnal district, respectively.